2021
DOI: 10.2217/fon-2021-0424
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy of Docetaxel Plus Nintedanib After Chemo-Immunotherapy Failure in Advanced Pulmonary Adenocarcinoma

Abstract: Aim: This real-world analysis evaluated docetaxel plus nintedanib in patients with advanced pulmonary adenocarcinoma after chemotherapy and immune checkpoint inhibitor failure, for whom treatment options are limited. Methods: Data were sourced retrospectively from seven German centers. Results: Of 93 patients, overall response rate was 41.4% (disease control rate: 75.9%). Of 57 patients given third-line docetaxel plus nintedanib, overall response rate was 50.0% (disease control rate: 82.7%). Median overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In this post hoc analysis, 14.9%/85.1% of patients received nintedanib plus docetaxel in the second line/third line or later; median PFS was 4.6 months, median overall survival was 8.8 months and the DCR was 78.2% [7]. Furthermore, the DCR in VARGADO cohort B was also consistent with that reported in other real-world analyses of third-line nintedanib plus docetaxel in advanced lung adenocarcinoma after failure on first-line chemotherapy and second-line ICI therapy (82e83%) [3,21]. A clear biological rationale for the use of anti-angiogenic agents (such as nintedanib) after ICI therapy is provided by the growing appreciation that angiogenesis and antitumour immunity are interlinked processes [8,9,22,23].…”
Section: Discussionsupporting
confidence: 80%
“…In this post hoc analysis, 14.9%/85.1% of patients received nintedanib plus docetaxel in the second line/third line or later; median PFS was 4.6 months, median overall survival was 8.8 months and the DCR was 78.2% [7]. Furthermore, the DCR in VARGADO cohort B was also consistent with that reported in other real-world analyses of third-line nintedanib plus docetaxel in advanced lung adenocarcinoma after failure on first-line chemotherapy and second-line ICI therapy (82e83%) [3,21]. A clear biological rationale for the use of anti-angiogenic agents (such as nintedanib) after ICI therapy is provided by the growing appreciation that angiogenesis and antitumour immunity are interlinked processes [8,9,22,23].…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, the VARGADO cohort demonstrated a mPFS of 6.4 months, with a 1-year OS rate of 52% in the third-line setting ( 16 ). Furthermore, another German cohort reported a mOS of 8.4 months in adenocarcinoma histology specifically ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, this is a single-center, retrospective analysis, and as such these observations should be confirmed in a prospective fashion. The Phase II Lung-Map S1800A study evaluated ramucirumab with pembrolizumab combination therapy compared to standard of care chemotherapy, of which two-thirds of the control arm received ram+doc, and was found to demonstrate an OS benefit ( 17 ). Post-hoc analyses will be required to understand the true PFS and OS estimates seen in this sub-group, however.…”
Section: Discussionmentioning
confidence: 99%
“…As LUME-Lung 1 was undertaken prior to the era of first-line ICIs, only limited data are available assessing the activity of nintedanib plus docetaxel following immunochemotherapy. Moreover, almost all studies undertaken to date have assessed nintedanib plus docetaxel in a third-line setting after successive chemotherapy and ICI monotherapy; in these studies, nintedanib plus docetaxel was associated with an unprecedentedly high response rate in this setting (36.5-58.3%), and encouraging PFS (3.2-6.4 months) (17)(18)(19)(20)(21). While these studies have demonstrated clinical activity of the combination, its activity following first-line immunochemotherapy is uncertain.…”
Section: Introductionmentioning
confidence: 99%